Industrial digital-green coupling transition in China: agricultural insights and broader implications - Shihui Hu; Guangxing Hu; Bin Li (Frontiers in Sustainable Food Systems)
This study examines the coupling relationship between digital transformation and green development in Chinese listed companies, with a particular focus on the agriculture and food industry from 2009 to 2022. Using principal component analysis (PCA) combined with TOPSIS and FEMA, the paper constructs a multidimensional measurement model to assess the coupling coordination degree between digital and green systems. The results reveal that overall coupling has significantly improved over time, especially in the service industry, while the agriculture sector shows a slower but upward trend due to digital infrastructure constraints. Digital transformation notably enhances green innovation and environmental performance, but challenges remain, such as strategic green innovation behaviors and financial policy gaps. The study highlights the need for targeted policies to bridge digital divides and promote substantive green innovation in agriculture and food sectors. These findings provide valuable insights for policymakers and corporate leaders aiming to accelerate the dual digital-green transformation in China's industrial sectors.